BACTERIOLOGICAL PROFILE AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF SURGICAL SITE INFECTIONS IN A TEACHING HOSPITAL - SUBHASHINI, B. S. V. V. (International Journal of Current Pharmaceutical Research, 2024)
Objective: Surgical site infections (SSI) are defined as infections occurring within 30 or 90 d after surgical operation or within 1 y, if an implant is left in place after procedure and affecting either incision or deep tissues at the operation site. SSI is one of the quality indicators of the healthcare system. Due to advent of newer antibiotics and emergence of multidrug-resistant bacteria, SSI requires reappraisal of the microbiological flora and in vitro antibiotic sensitivity pattern. The aim of the present study is to determine the incidence etiology of SSI, and determine their Antibiogram. Methods: Cross-sectional study conducted for a period of three months from January 2024 to March 2024. A total of fifty swabs/pus specimens from various types of surgical sites suspected to be infected on clinical grounds were collected from the post-operative wards of surgical departments and processed in Microbiology laboratory. Isolation and identification of bacterial agents were done as per standard protocols. Antimicrobial susceptibility testing was performed by Kirby-Bauer’s disc diffusion method. Results: Out of 50 samples, 32 were culture-positive. 87.50% showed monomicrobial growth and 12.50% showed polymicrobial growth. Analysis of bacterial profile shows Staphylococcus aureus (27.77%) was the predominant isolate, followed by Pseudomonas aeruginosa (19.44%) and Escherichia coli (19.44%). Antibiogram of gram-positive isolates showed sensitivity to Teicoplanin, Vancomycin, and linezolid, whereas gram-negative isolates were sensitive to Meropenem, Piperacillin-tazobactam and levofloxacin. Conclusion: Status of SSI is the main quality indicators of hospital infection control and prevention measures. Continuous surveillance on etiology and antibiogram of SSI is necessary to monitor antimicrobial resistance and guide in empirical treatment.